PREPARATION OF MSMEs FINANCIAL STATEMENTS - Yusup, Bahrudin Fany El; Kholilah, Kholilah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
MSMEs in Dapur Catering still maintain basic financial records. Using the BukuKas app, daily transactions are first recorded before creating MSMEs financial statements. This study is a qualitative case study. Interviews, observation, documentation, and literature reviews are data collection method in this research. Data analysis includes reduction, data visualization, and conclusion. This study used triangulation of data sources by comparing the interview findings of each informant to find similar replies and comparing the interview results with observations. Making a list of accounts, an initial balance sheet, a list of fixed assets, a general journal, an adjustment journal, a general ledger, and financial statement are the following steps in the accounting cycle. Statements of Financial Position, Income Statements, and Notes to Financial Statements make up the SAK EMKM-compliant design of financial statements. The limitation of the study is that because the transaction lasted only one month, only a portion was covered. Future research might include a greater number of transactions and extended observation times.